Endoscopic grading of gastric intestinal metaplasia using blue light imaging in a low-risk population: Multicenter cross-sectional validation study - Rodriguez-Carrasco, Marta; Esposito, Gianluca; Dilaghi, Emanuele; Manfredi, Guido; Alicante, Saverio; Buscarini, Elisabetta; Annibale, Bruno; Dinis-Ribeiro, Mário (Endoscopy International Open, 2025)
Detecting gastric intestinal metaplasia (GIM) with white light endoscopy (WLE) remains a challenge and virtual chromoendoscopy methods have been shown to increase accuracy. We aimed to externally validate the Endoscopic Grading of Gastric Intestinal Metaplasia (EGGIM) using blue light imaging (BLI).First, the reliability of BLI and the EGGIM score was evaluated through assessment of 90 images divided into three sets of 30. A multicenter cross-sectional study was conducted at two Italian centers involving 102 patients (510 biopsies). Both per-biopsy and per-patient analyses were performed to ascertain accuracy of BLI in detecting and staging GIM (vs. histology).BLI significantly enhanced interobserver agreement of endoscopic diagnosis of GIM, with a Fleiss Kappa of 0.4 (95% confidence interval [CI] 0.3–0.5), compared to 0.2 (95% CI 0.2–0.3) with WLE. Concordance was particularly strong in applying the EGGIM score (weighted Kappa 0.7; 95% CI 0.5–0.9). BLI showed significant improvements in sensitivity over WLE, with an increase observed in both per-biopsy analysis (82%; 95%CI 73.7–89.0 vs. 50%;95% CI 40.6–60.3) and per-patient analysis (96%; 95% CI 84.5–99.4 vs. 68%;95% CI 52.4-81.4). The area under the curve of EGGIM in diagnosing OLGIM III/IV was 0.9 (95% CI 0.8–1.0), confirming EGGIM > 4 being the optimal threshold (sensitivity of 80%, specificity of 88%).Our study validates BLI integrated with the EGGIM system as an effective strategy, highlighting its precision in identifying advanced GIM stages. BLI's notable sensitivity enhances its use as a complementary tool to WLE, significantly improving gastric cancer risk assessment.
Keywords: Endoscopy Upper GI Tract; Precancerous conditions & cancerous lesions (displasia and cancer) stomach; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE); Endoscopic resection (ESD, EMRc, ...)